Severe antithrombin deficiency in pregnancy: Achieving adequate anticoagulation. (March 2019) - Pearson-Stuttard, Ben; Bagot, Catherine; Ciantar, Etienne; Myers, Bethan; Davies, Rosalyn; Rayment, Rachel; Clark, Amanda; McKernan, Angela; Pavord, Sue
Antithrombin deficiency is identified as one of the most potent risk factors for venous thromboembolism during pregnancy. Therapeutic low molecular weight heparin is recommended, but it can be difficult to attain sufficient anticoagulation since low molecular weight heparin requires antithrombin to exert its anticoagulant effect. We carried out a multicentre case-series assessing the dose of low molecular weight heparin required to achieve therapeutic anti-activated factor X levels in pregnant women with antithrombin deficiency. We assessed 27 pregnancies in 18 women with severe antithrombin deficiency, which we defined as an antithrombin level of <0.55 IU/ml (with or without prior venous thromboembolism) or an antithrombin level < 0.8 IU/ml and a personal history of venous thromboembolism. Our data illustrate the need for high doses of low molecular weight heparin to achieve therapeutic anti-activated factor X levels (average 20, 220 IU/day). All pregnancies ended in live birth (excluding one elective termination), although intrauterine growth restriction occurred in five (18%).